Study on Phase Transition Mechanism of Polymer Composite Cold Thermal Energy Storage Agent Based on Molecular Dynamics Simulation - Chen Youliang; Sheng Wei; Wang Ruirui; Li Xueli; Hao Xiaoru; Zheng Haikun (Zhileng xuebao)
Composite phase-change cold thermal energy storage materials have attracted significant attention in recent years; however, studies on their microscopic phase-change mechanism have garnered insignificant interest. In this study, the ice-water system with a high latent heat was mixed with polyethylene glycol (PEG) of mass fractions of 0%, 3%, and 5%, and using 10% glycerol and 20% ammonium chloride as the nucleating and cooling agents, respectively. The molecular dynamics method was used to simulate the phase transition process. The phase transition temperature was predicted and analyzed based on parameters such as the bonding and conformation, bond length, bond angle, radial distribution function, diffusion coefficient, and density. The results demonstrate that the lower the temperature, the lower the molecular kinetic energy, the smoother the molecular motion, and the greater the probability that the hydroxyl bond length will decrease. The temperature had a slight effect on the bond angle but a great impact on the bond length. With regard to the phase change, as the temperature decreased, the diffusion coefficient of the solution system decreased; the density increased; the solution viscosity increased; the orderliness increased. In the 10% glycerol-20% ammonium chloride aqueous system, the inflection point of the phase transition temperature was 255.2–256 K, which is very close to the experimental result of 255.5 K. After adding 3% and 5% PEG polymers, the phase transition temperature of the solution system was predicted to be 254.1–254.3 K and 253.5–253.8 K, demonstrating a decrease of 1.1–1.7 K and 1.7–2.2 K, respectively.